1991
DOI: 10.1002/ijc.2910480505
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of nuclear DNA content in human neuroepithelial tumors

Abstract: The relationship between survival and flow cytometric DNA-ploidy and other prognostic factors such as histological subtype, anatomical tumor site, patient sex and age was investigated in 153 patients with intracranial neuroepithelial tumors who underwent surgical treatment. We found a trend toward poorer survival from anaplastic astrocytomas and glioblastomas with respect to low-grade (I and II) astrocytomas (which did not differ significantly); accordingly, patients were grouped into these 3 histologic subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…Like with several other variables, conclusions about ploidy as a prognostic variable in astrocytic tumors are mixed and are sometimes contradictory. Whereas a number of investigators found that aneuploidy was associated with shorter survival,33, 34, 46–48 others found no association,49 and still others observed longer survivals 15, 50. In our series, aneuploidy was associated with younger patient age and longer survival time.…”
Section: Discussioncontrasting
confidence: 59%
“…Like with several other variables, conclusions about ploidy as a prognostic variable in astrocytic tumors are mixed and are sometimes contradictory. Whereas a number of investigators found that aneuploidy was associated with shorter survival,33, 34, 46–48 others found no association,49 and still others observed longer survivals 15, 50. In our series, aneuploidy was associated with younger patient age and longer survival time.…”
Section: Discussioncontrasting
confidence: 59%
“…Aberrations in the DNA content (ploidy) or increase in DNA synthesis during the S and G 2 -M phases of the cell cycle can be evaluated rapidly by DNA-FC. Oncological studies have shown that 30 to 80% of all malignant gliomas have aneuploid cell populations (4,7,8,13), and for gliomas with normal ploidy, elevated percentages of cells in S and G 2 -M phases have been correlated with poor outcome (6,21,27). Consequently, malignant tissue can be identified by the presence of aneuploid populations of cells and/or by the presence of an elevated level of S phase and G 2 -M phase cells.…”
mentioning
confidence: 96%
“…While it is well defined that well differentiated tumors (A) are diploid [15,30], in dealing with high-grade gliomas, the results vary in the different series. Some authors could not find a prognostic relationship between ploidy and tumor progression [15], whereas in other reports diploid and tetraploid tumors are associated with a better prognosis [13,14]. Studies are discrepant, and some authors find that diploidy in GBM means a quicker progression [31].…”
Section: Discussionmentioning
confidence: 98%
“…radiotherapy, patient's age, or Karnofsky score [10][11][12]. There are also a few studies on the DNA pattern measured by flow cytometry [13][14][15] or by image analysis [16][17][18], but the results are inconclusive, whereas some authors find a high correlation between ploidy and prognosis, the relationship seems to be lost in multivariate analysis.…”
mentioning
confidence: 99%